2020
DOI: 10.1088/2399-6528/ab7b32
|View full text |Cite
|
Sign up to set email alerts
|

Pre-breakdown phenomena in hydrocarbon liquids in a point-plane gap under step voltage. Part 2: behaviour under negative polarity and comparison with positive polarity

Abstract: This study addresses the dielectric performance of nonpolar hydrocarbon liquids and mineral oils under negative polarity stress. Stopping length for non-breakdown streamers, breakdown voltages and velocities for various pre-breakdown streamer modes have been studied for a selection of model liquids (cyclohexane and white oils), for a gas to liquid oil, and a refined naphthenic transformer oil. Studies of propagation modes were done using an 80 mm point to plane gap and a step voltage with 0.5 μs rise time. Lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 40 publications
(87 reference statements)
2
8
0
Order By: Relevance
“…Negative streamers are strange: streamer shape for a given mode is close to the same through all liquids tested in [16], and here it is found that increased pressure has virtually no effect on streamer shape or velocity, either. Breakdown voltage only increased a factor of 2 for negative streamers compared to 5 for the positive ones over the investigated pressure range.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Negative streamers are strange: streamer shape for a given mode is close to the same through all liquids tested in [16], and here it is found that increased pressure has virtually no effect on streamer shape or velocity, either. Breakdown voltage only increased a factor of 2 for negative streamers compared to 5 for the positive ones over the investigated pressure range.…”
Section: Discussionsupporting
confidence: 57%
“…Permission from IEEE must be obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works." There are lots of current pulses during negative 1 st mode, and they have corresponding light pulses [16]. While the typical "reillumination" is from 0.5 A and upwards, most of these pulses are much smaller.…”
Section: Negative Streamersmentioning
confidence: 99%
See 2 more Smart Citations
“…This frequent filtering may not have been necessary for positive streamers, but certainly was for negative ones. This is described in detail in part 2 of this paper [32], which focuses on negative streamers.…”
Section: Liquid Treatmentmentioning
confidence: 99%